Soccer Metaphors in Brazilian Portuguese: A Cognitive Perspective - Bezerra Ferreira, José Genival (Lingüística y Literatura, 2018)
This work is a qualitative analysis of metaphoric expressions in Brazilian soccer with reference to the Soccer World Cup, which took place in Brazil, in 2014. The essence of this theme was addressed in articles collected from websites. Based on the foundation of presumption theory of Cognitive Linguistics with emphasis in the theory of Conceptual Metaphor, the study showed that the construction of metaphors, in Brazilian Portuguese, connected to soccer, will develop different expressions, such as: «soccer is war», «soccer is politics», and therefore making them reflect in the importance of this sport in building the identity of the Brazilian people.